The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1186/s40557-017-0170-3
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to occupational hazards for pregnancy and sick leave in pregnant workers: a cross-sectional study

Abstract: BackgroundThis study aimed to investigate the association between exposure to occupational hazards for pregnancy and sick leave (SL) in pregnant workers.MethodsA cross-sectional study was performed in French occupational health services in 2014. Occupational hazards for pregnancy were assessed by occupational health physicians (OHPs). After delivery and at the time of returning to work, 1,495 eligible workers were interviewed by OHPs. Information on SL was self-reported. Risk ratios (RRs) were calculated from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 36 publications
1
13
0
1
Order By: Relevance
“…The study by Kristensen et al (2008) indicated that ergonomic adjustments to workstations reduced absenteeism. These findings are consistent with several other studies, which have shown that absence during pregnancy is highly correlated with working conditions (Hansen et al 2015;Henrotin et al 2017;Kaerlev et al 2004). Other benefits, including the working atmosphere, the quality of working relationships, employee motivation, and the quality of their work, are more difficult to put a number on but are not less valuable.…”
Section: Findings and Actions On Effectssupporting
confidence: 92%
See 1 more Smart Citation
“…The study by Kristensen et al (2008) indicated that ergonomic adjustments to workstations reduced absenteeism. These findings are consistent with several other studies, which have shown that absence during pregnancy is highly correlated with working conditions (Hansen et al 2015;Henrotin et al 2017;Kaerlev et al 2004). Other benefits, including the working atmosphere, the quality of working relationships, employee motivation, and the quality of their work, are more difficult to put a number on but are not less valuable.…”
Section: Findings and Actions On Effectssupporting
confidence: 92%
“…Bilhartz and Bilhartz 2013;Cheng et al 2009), but this topic is generally less investigated than outcomes pertaining to pregnancy and children's health (Figà-Talamanca 2006). However, consistent evidence indicates that occupational exposures and arduous working conditions lead to a higher rate of sick leave during pregnancy (Dørheim et al 2013;Hansen et al 2015;Henrotin et al 2017;Kaerlev et al 2004). Many countries have implemented specific laws to protect pregnant women and their unborn children from occupational exposure, in accordance with the International Labour Organization's Maternity Protection Convention, 2000 (No.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between occupational exposures and absence from work during pregnancy has mostly been assessed for individual factors, one at a time, rather than for combinations of exposures. However, one crosssectional study investigated an index of occupational exposures and showed that, with an increasing number of exposures, the risk of self-reported sickness absence during pregnancy increased (6). Findings described in a Danish report indicated that pregnant women concurrently exposed to several occupational exposures had more absences from work than pregnant women with fewer or no exposures at work (7).…”
mentioning
confidence: 99%
“…Доказано, что значительное количество заболеваний репродуктивной системы являют-ся профессионально обусловленными, приводя к проблемам с зачатием, вынашиванием плода и даже к бесплодию [6,7,10,14]. Особую тре-вогу вызывают профессии высокого риска, в которых женщины подвергаются сочетанному действию профессиональных факторов различ-ной природы (например, воздействие химиче-ских веществ в сочетании с физическими, био-логическими факторами, тяжестью и напря-женностью труда) [12,15].…”
unclassified